Malignant conversion of chemically transformed normal human cells. - Milo, G E (1996)
Two structurally unrelated chemicals, aflatoxin B1 and propane sultone, transformed human foreskin cells to a stage of anchorage-independent growth. Isolation from agar and repopulation in monolayer culture of these transformed cells was followed by transfection with a cDNA library, which resulted in cells that exhibited an altered epithelioid morphology. Chemically transformed/nontransfected cells and transfected normal cells did not undergo a significant morphological change. These epithelioid-appearing, transfected cells, when inoculated into nude mice, form progressively growing tumors. The tumors are histopathologically interpreted as carcinomas. All of the first generation tumors in the surrogate hosts exhibited characteristic rates of growth similar to those of transplants of spontaneous human tumors. In the second generation of tumor xenografts, the progressively growing tumors derived from the transfected cells exhibited a more rapid rate of growth. Southern analysis and reverse transcription PCR confirmed that a 1.3-kb genetic element was integrated into the genome and was actively being transcribed. Examination of the metaphase chromosomes in normal human cells revealed that the genetic element responsible for this conversion was located at site 31-32 of the q arm of chromosome 7. The DNA sequence of this 1.3-kb genetic element contains a coding region for 79 amino acids and a long 3'-untranslated region and appears to be identical to CATR1.3 isolated from tumors produced by methyl methanesulfonate-converted, nontransplantable human tumor cells.